Targeting serum phosphate trajectory stratification to improve outcomes in high-risk Cardiovascular-Kidney-Metabolic-Sepsis cohorts - Jinwei Dai; Wenye Xu; Nianzhe Sun; Ting Wu; Zhaoxin Qian; Zhihong Zuo (PLoS ONE, 2025)
Background Sepsis patients exhibit complex clinical conditions, frequently complicated with metabolic dysregulation. Cardiovascular-Kidney-Metabolic Syndrome (C-K-M) is classified as below: stage 0, no C-K-M risk factors; stage 1, excess or dysfunctional adiposity; stage 2, metabolic risk factors (hypertriglyceridemia, hypertension, diabetes, metabolic syndrome) or moderate- to high-risk chronic kidney disease; stage 3, subclinical cardiovascular diseases (CVD) in C-K-M syndrome or risk equivalents (high predicted CVD risk or very high-risk chronic kidney diseases); and stage 4, clinical CVD in C-K-M syndrome. While high-risk patients defined by C-K-M criteria often have poor outcomes, studies seldom have classified these patients into subtypes based on metabolic profiles. Serum phosphate, recently recognized as a potential metabolic and organ function marker, has unclear dynamic trajectories and prognostic significance across high-risk CKM-sepsis subgroups. Purpose This study aimed to evaluate the association between serum phosphate trajectories and clinical prognosis, specifically 28-day mortality, among high-risk C-K-M-sepsis patients and across various subgroups. Methods We extracted data for high-risk C-K-M-Sepsis patients from the MIMIC-IV database. After developing a simplified C-K-M staging system, we used unsupervised consensus clustering to identify four metabolic phenotypes. Serum phosphate trajectories during the first seven ICU days were summarized by daily earliest measurements. Associations between phosphate trajectory clusters and 28-day ICU mortality were examined using multivariable logistic regression, inverse probability weighting (IPW) derived from propensity scores, and doubly robust estimation. Subgroup analyses stratified by age, sex, and key comorbidities were conducted, and results were visualized as forest plots. Results Multivariate analysis revealed that trajectory Group 3 (persistently high serum phosphate) had significantly increased mortality risk (OR=2.909, 95% CI: 2.121–2.991, p < 0.001). Elevated risk was prominent in younger (<65 years) and male subgroups. Comorbidity analysis identified CVA and COPD as significant risk factors. Conclusion Serum phosphate trajectory patterns significantly correlate with 28-day mortality in high-risk CKM-sepsis patients, highlighting potential distinct metabolic phenotypes. Early intervention targeting serum phosphate levels may improve prognosis in high-risk subgroups.